Effect of Sowing Time Based Temperature Variations on Growth, Yield and Seed Quality of Garden Pea - Ali, MZ; Aziz, MA; Sarker, MAI; Mazumder, S; Paul, SK; Mujahidi, TA; Khan, MSA; Bhuiyan, MS (Bangladesh Agronomy Journal, 2016)
A field experiment was conducted at the research field of Agronomy Division, BARI, Joydebpur, Gazipur and ARS, Burirhat, Rangpur to evaluate crop growth, yield and seed quality of garden pea in prevailing temperature at different sowing dates (10 November, 20 November, 30 November, 10 December, 20 December and 30 December). Sowing date based temperature variations significantly affected the crop growth, TDM production, yield and seed quality of BARI Motorshuti-3. Plants with November 20-30 sowing performed the best in respect of yield and yield contributing characters. However, with the delayed in sowing dates, the temperatures at the later growth phases were increased, while the grain growth duration, grain yield and grain quality decreased substantially. Results revealed that November 20-30 would be the optimum time of sowing for maximum yield with quality seed production of garden pea in Bangladesh. Bangladesh Agron. J. 2016, 19(1): 29-36